Types I and V Anti-CRISPR Proteins: From Phage Defense to Eukaryotic Synthetic Gene Circuits - Yu, Lifang; Marchisio, Mario Andrea (Frontiers in Bioengineering and Biotechnology, 2020)
CRISPR (clustered regularly interspaced short palindromic repeats)-Cas (CRISPR-associated proteins), a prokaryotic RNA-mediated adaptive immune system, has been repurposed for gene editing and synthetic gene circuit construction both in bacterial and eukaryotic cells. In the last years, the emergence of the anti-CRISPR proteins (Acrs), which are natural OFF-switches for CRISPR-Cas, has provided a new means to control CRISPR-Cas activity and promoted a further development of CRISPR-Cas-based biotechnological toolkits. In this review, we focus on type I and type V-A anti-CRISPR proteins. We first narrate Acrs discovery and analyze their inhibitory mechanisms from a structural perspective. Then, we describe their applications in gene editing and transcription regulation. Finally, we discuss the potential future usage—and corresponding possible challenges—of these two kinds of anti-CRISPR proteins in eukaryotic synthetic gene circuits.